Multispectral label-free in vivo cellular imaging of human retinal pigment epithelium using adaptive optics fluorescence lifetime ophthalmoscopy improves feasibility for low emission analysis and increases sensitivity for detecting changes with age and eccentricity - Kunala, Karteek; Tang, Janet A. H.; Parkins, Keith; Hunter, Jennifer J. (Journal of biomedical optics, 2024)
Adaptive optics fluorescence lifetime ophthalmoscopy (AOFLIO) provides a label-free approach to observe functional and molecular changes at cellular scale . Adding multispectral capabilities improves interpretation of lifetime fluctuations due to individual fluorophores in the retinal pigment epithelium (RPE). To quantify the cellular-scale changes in autofluorescence with age and eccentricity due to variations in lipofuscin, melanin, and melanolipofuscin in RPE using multispectral AOFLIO. AOFLIO was performed on six subjects at seven eccentricities. Four imaging channels ( ) were used: 473/SSC, 473/LSC, 532/LSC, and 765/NIR. Cells were segmented and the timing signals of each pixel in a cell were combined into a single histogram, which were then used to compute the lifetime and phasor parameters. An ANOVA was performed to investigate eccentricity and spectral effects on each parameter. A repeatability analysis revealed change in lifetime parameters in repeat visits for 532/LSC. The 765/NIR and 532/LSC had eccentricity and age effects similar to previous reports. The 473/LSC had a change in eccentricity with mean lifetime and a phasor component. Both the 473/LSC and 473/SSC had changes in eccentricity in the short lifetime component and its relative contribution. The 473/SSC had no trend in eccentricity in phasor. The comparison across the four channels showed differences in lifetime and phasor parameters. Multispectral AOFLIO can provide a more comprehensive picture of changes with age and eccentricity. These results indicate that cell segmentation has the potential to allow investigations in low-photon scenarios such as in older or diseased subjects with the co-capture of an NIR channel (such as 765/NIR) with the desired spectral channel. This work represents the first multispectral, cellular-scale fluorescence lifetime comparison in the human RPE and may be a useful method for tracking diseases.